Improving Students' Understanding of Chemistry Concepts Through Project-Based Learning (PJBL): A Systematic Literature Review - Rahmawan, Setia; Nur Fadhilah, Septy; Fackhurohman, Edi (Universitas Islam Lamongan, 2025)
One of the obstacles in chemistry learning is the large number of complex concepts, especially material that cannot be observed directly by students. Abstract and unobservable chemistry concepts often pose a major challenge in learning, resulting in low student comprehension and difficulty in relating theory to practice. PJBL is a learning model that allows students to gain direct experience with the chemistry concepts they encounter. This systematic literature review aims to synthesize existing research on the effectiveness of the PJBL model in improving the understanding of chemistry concepts. This type of research is a literature study using the Systematic Literature Review (SLR) method on 10 articles from 2015 to 2024 to evaluate the effectiveness of the Project Based Learning (PJBL) model in improving the understanding of chemistry concepts. Based on several articles, the results show that PJBL consistently produces a significant increase in conceptual understanding, as demonstrated by an increase in student N-gain scores in the moderate to high categories, as well as encouraging learning achievement in repetitive learning. The main contribution of SLR in this study is to provide an integrated and structured summary that can be used as a practical reference for educators in designing contextual and applicable project-based learning models. This study supports the integration of PJBL in learning to strengthen student engagement and deep conceptual understanding